Exploring the perceived effectiveness of a life skills development program for high-performance athletes - Hardcastle, Sarah; Tye, Marian; Glassey, R.; Hagger, Martin (Elsevier BV, 2015)
The purpose of this study was to explore attitudes towards, experiences of, and perceived effectiveness of a life-skills programme for high-performance young athletes from multiple perspectives, including the athletes, coaches, parents, programme facilitators, and sport administrators. Six focus groups were conducted with 54 high-performance athletes from six sports: squash, softball, baseball, netball, triathlon, and surfing. Three focus groups were conducted with parents (n = 8) of athletes and a further eight semi-structured interviews were conducted with coaches (n = 4) and lead facilitators (n = 4) of the life-skills programme. Four semi-structured interviews were also held with representatives from State Sporting Associations (SSAs) from the sports involved. Thematic content analysis revealed seven main themes: achieving balance and managing stress, time management, goal setting, confidence and control, information overload and repetition, credible role-models, coach reinforcement and follow-up. The programme was perceived to be moderately successful in developing adaptive behaviours and motives including better engagement in training and in adopting time management and planning skills in contexts outside of sport such as homework and academic study. The programme also fostered the development of skills, attitudes, and motives important for sport success such as goal setting and having confidence to succeed. To improve the effectiveness of such programmes, more emphasis should be placed on the practice of, and engagement with, applied techniques to develop skills with less emphasis on information giving and theory. Facilitators of programmes should also be more pro-active in involving parents and coaches as a way to improve continuity and provide post-program reinforcement and support.